Factors predisposing to postural hypotensive symptoms in the treatment of high blood pressure. Issue 10 (October 1975) - Talbot, S; Smith, A J
Abstract : Symptoms due to orthostatic and exertional hypotension occurred in 23-4 per cent of 448 hypertensive patients treated with guanethidine, debrisoquine, or bethanidine. Symptoms were significantly more frequent in patients treated with guanethidine than in those treated with bethanidine or debrisoquine. Women rather than men and patients with radiological evidence of cardiomegaly, electrocardiographic evidence of left ventricular hypertrophy, or ST/T wave changes, developed these symptoms significantly more often than other patients. A raised blood urea was found more frequently in patients with postural hypotensive symptoms. Characteristically guanethidine produced early morning postural hypotensive symptoms, wheras hypotensive symptoms caused by bethanidine and debrisoquine occurred at other times of the day and particularly one to two hours after tablet ingestion. Debrisoquine and guanethidine had a significantly greater negative chronotropic effect than bethanidine. It is suggested that negative chronotropic effects of these drugs may potentiate hypotensive symptoms in patients with cardiovascular, renal, or cerebrovascular disease. It should be possible to minimize symptoms of postural hypotension by attention to predisposing factors and selection of treatment accordingly.